Question Number 171999 by Mikenice last updated on 23/Jun/22
$${resolve}: \\ $$$$\frac{\mathrm{4}\left({x}−\mathrm{4}\right)}{{x}^{\mathrm{2}} −\mathrm{2}{x}−\mathrm{3}}\:{into}\:{partial}\:{fraction} \\ $$
Answered by Rasheed.Sindhi last updated on 23/Jun/22
$$\frac{\mathrm{4}\left({x}−\mathrm{4}\right)}{\left({x}−\mathrm{3}\right)\left({x}+\mathrm{1}\right)}=\frac{{a}}{{x}−\mathrm{3}}+\frac{{b}}{{x}+\mathrm{1}} \\ $$$$\mathrm{4}\left({x}−\mathrm{4}\right)={a}\left({x}+\mathrm{1}\right)+{b}\left({x}−\mathrm{3}\right) \\ $$$${x}=\mathrm{3}:\:\mathrm{4}\left(\mathrm{3}−\mathrm{4}\right)=\mathrm{4}{a}\Rightarrow{a}=−\mathrm{1} \\ $$$${x}=−\mathrm{1}:\:\mathrm{4}\left(−\mathrm{1}−\mathrm{4}\right)=−\mathrm{4}{b}\Rightarrow{b}=\mathrm{5} \\ $$$$\frac{\mathrm{4}\left({x}−\mathrm{4}\right)}{\left({x}−\mathrm{3}\right)\left({x}+\mathrm{1}\right)}=\frac{−\mathrm{1}}{{x}−\mathrm{3}}+\frac{\mathrm{5}}{{x}+\mathrm{1}} \\ $$$$ \\ $$